1997
DOI: 10.1007/bf03341098
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Pathways to Student Expulsion: Consideration of Individual and System Indicators

Abstract: Paralleling the implementation of "zero-tolerance" disciplinary policies with regard to weapons possession and threats to student and faculty safety on campus, there has been a significant increase in the number of students being expelled from schools. This paper provides descriptive information about the incidence of expulsions from one school district. A categorization system is presented which provides a way for school psychologists to capture the complexity of student characteristics and family and schooli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…In contrast to suspension, school expulsion tends to be used relatively infrequently (Sinclair, 1999). Morrison and colleagues (1997) report that expulsion appears to be reserved for incidents of moderate to high severity of troublesome or dangerous behaviors. A limited number of studies have focused on the associations between involvement in school discipline and the antisocial behavior trajectory.…”
Section: Environmental and Individual Characteristics Influencing Antisocial Behaviormentioning
confidence: 99%
“…In contrast to suspension, school expulsion tends to be used relatively infrequently (Sinclair, 1999). Morrison and colleagues (1997) report that expulsion appears to be reserved for incidents of moderate to high severity of troublesome or dangerous behaviors. A limited number of studies have focused on the associations between involvement in school discipline and the antisocial behavior trajectory.…”
Section: Environmental and Individual Characteristics Influencing Antisocial Behaviormentioning
confidence: 99%
“…One expert in California reported that the main appeals issue facing a large county schools office is that site-based school officials do not know how to build "evidence-based cases" and conduct hearings about expulsion matters (P. Kauble, personal communication, Mar. 9,2001). Not surprisingly, these officials are not lawyers, and yet they are being asked to conduct complex legal procedures.…”
Section: Legal a D Policy Impiicatiomf6r Expillfion As An Eventmentioning
confidence: 99%
“…Morrison, D'Incau, Couto, and Loose (1997) reported that expulsion appears to be reserved for incidents of moderate to high severity, although there is some doubt as to whether students who are expelled are always those who are the most troublesome or dangerous. Zero tolerance policies, mandating expulsion for certain types of events, have apparently led to the expulsion of many children and youths who would be considered "good students.…”
mentioning
confidence: 93%